Caregiver burden in cerebral palsy and its impact on the caregivers - Wijesinghe, C.J (My University, 2008)
The objectives o(this research were to develop a valid and a reliable instrument to assess the caregiver burden experienced by caregivers of children with cerebral palsy and to assess the caregiver burden of principal caregivers of such children in the Galle District, their psychological problems and the predictors of the psychological problems. Phase I of the study developed and validated a self administered, 25 item, multidimensional scale - the Caregiver Difficulties Scale (CDS) - to assess the level of caregiver burden experienced by the principal caregivers of children with cerebral palsy, in a hospital setting. Phase II of the study assessed the level of caregiver burden experienced by a sample 375 principal caregivers attending the Teaching Hospital (TH), Karapitiya, using the CDS. The prevalence of psychological problems of these caregivers was calculated using the General Health Questionnaire (GHQ). The predictors of psychological problems in caregivers were determined Using a logistic regression analysis, with a special emphasis on caregiver burden. The logistic regression analysis identified 5 predictors of psychological problems in the caregivers. The strongest predictor for presence of psychological problems was the level of caregiver burden (pO.OO I). The educational level of the caregiver and the age of the child (pO.OO I) were also predictive or the psychological problems (pO.OO I).